Забезпечення правової освіти громадськими організаціями: теоретико-правовий аспект - Потапенко, Н.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассмотрено формирование гражданского общества как естественной потребности общественности при существенных изменениях в отношениях между личностью, государством и обществом. Анализируются факторы, которые влияют на его формирование, создание условий для повышения уровня правовой культуры населения. In the article is revealed the formation of the civil society in modern Ukraine, that became a natural wed of the public under important changes at relations between a person, state and society. In the article are given the factors, which influence its formation and it is referred to the formation of conditions for the increase of the law culture level of population.